Exploring left atrium volumetric rates derived from cardiovascular magnetic resonance feature tracking imaging in paroxysmal atrial fibrillation. (10th June 2022) - Mojica Pisciotti, M; Panovsky, R; Holecek, T; Masarova, L; Pesl, M; Starek, Z; Feitova, V; Opatril, L; Kincl, V
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): 1. European Regional Development Fund - Project ENOCH (No. CZ.02.1.01/0.0/0.0/16_019/0000868) 2. Specific University Research provided by MŠMT, No.: MUNI/A/1462/2021 Background: Cardiac magnetic resonance feature tracking (CMR-FT) allows a quantitative analysis of regional heart deformation and understanding several diseases' underlying mechanisms. Paroxysmal atrial fibrillation (PAF), defined as recurrent arrhythmic episodes that terminate spontaneously, may induce early changes in the left atrial (LA) wall, which CMR-FT can detect. Thus, the LA function assessment may help early identification of PAF via imaging markers. Purpose: Evaluate the left atrial volumetric change rate in PAF patients during the reservoir and contractile LA phases. Methods: The local Ethics Committee approved the study following the Declaration of Helsinki (2000) of the World Medical Association. A group of 50 subjects (27 PAF patients and 23 controls (CG)) were examined with CMR. The analyses were performed using CMR-FT commercial software (2D CPA MR, TomTec v4.6.4.40, Germany). Left ventricle (LV) and left atrial (LA) volume curves were obtained from analyzing long-axis cine images (50 frames per cardiac cycle). Corresponding slopes in the reservoir-LV emptying (LVemp) and LA filling (LAfill) volume rate-and contractile-LV filling (LVfill) and LA emptying (LAemp) volume rate-phases were calculated. Negative slope values imply blood volume decreasing with time. The LA longitudinal strain (LS) was also assessed. All statistical data analyses were done in RStudio (R, v4.0.3). Results: PAF patients have a significatively higher LAfill and lower LAemp than controls in the reservoir and contractile phases (LAfill 129.1±32.6 ml/s vs 101.4±22.8 ml/s, P<0.001 and LAemp -154.1±54.0 ml/s  vs -116.2±40.4 ml/s, P=0.007). In contrast, the LV volumetric rates were similar in both phases (LVemp -311.3±79.2 ml/s vs -280.3±62.1 ml/s, P=0.128 and LVfill 199.4±75.6 ml/s vs 190.0±62.8 ml/s, P=0.631, respectively). The volumetric rates significantly correlated for PAF patients (reservoir (LVemp and LAfill) r = -0.54, P = 0.003 and contractile (LVfill and LAemp) r = -0.64, P < 0.001), but not for controls. The LS was also impaired in PAF patients vs controls (reservoir 26.1% (21.5% to 30.5%) vs 32.7% (28.1% to 39.1%),  P = 0.001 and contractile 10.5% (8.8% to 13.3%) vs 14.9% (12.1% to 19.7%),  P = 0.003). Conclusion: The LA volumetric rates suggest a possible compensation mechanism that allows the LA to deform faster or slower enough to receive or release blood volume during the LA phases; PAF patients' LA receives more blood in a fixed time interval. Their LA cavity could experience pressure or volume overload, allowing LA enlargement. Likewise, the LA emptying (contractile) was slower in PAF patients, which means they release less blood than controls in a given time. Consequently, the PAF patient's LA holds a higher blood volume during the whole cardiac cycle. However, other explanatory factors should be independently assessed. The volumetric rates assessment through CMR-FT could help identify early changes in the LA deformation in PAF patients.